INTEGRASI PENGAJARAN DI SANGGAR NONFORMAL DAN PELESTARIAN BUDAYA MELALUI PEMBUATAN BATIK CELUP PADA KOMUNITAS ANAK-ANAK PMI DI MALAYSIA - Subekti, Shellien Arik; Rosida (Environmental Engineering Journal of Community Dedication, 2025)
This community service program aims to provide access to non-formal education for children of irregular Indonesian Migrant Workers (PMI) in Tanjung Malim, Malaysia, who experience limited formal education and connection to Indonesian culture. Using a Participatory Action Research (PAR) approach, the program includes identification of student needs, teaching of eight academic subjects, and cultural preservation through batik dyeing. The program is designed to improve students' academic skills, introduce Indonesian traditional arts, and instill national values through creative and interactive activities. Results showed an improvement in students' academic skills, learning motivation, and self-confidence. In addition, cultural preservation activities succeeded in fostering a sense of pride in Indonesian traditions. For sustainability, it is recommended to improve learning facilities, train studio managers, and develop culture-based programs. This approach has proven effective in creating social and educational impacts for the PMI community.